2021
DOI: 10.51791/njap.v39i2.757
|View full text |Cite
|
Sign up to set email alerts
|

Physiological evaluation of broiler finishers fed fermented bovine blood and rumen digesta meal

Abstract: A 35-day feeding trial involving three hundred (300) five (5) week old broilers was carried out in a completely randomized design to evaluate the haematology, serum biochemical and gastro-intestinal characteristics of broiler finishers fed diets containing a mixture of fermented bovine blood and rumen digesta (FBBRD) meal at dietary levels of 0, 5, 10, 15 and 20 %, respectively. The birds were randomly grouped into five, with sixty birds each and four replicates of fifteen birds per treatment. At the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Yitbarek et al (2016) showed that carcass characteristics of birds fed diets containing different levels of DBRCM were not statistically different in edible carcass yield comparing with the control group. Also, Esonu et al (2011) found that there were no significant differences in dressing percentage of birds fed diets containing mixture of fermented bovine blood and rumen digesta. Onu et al (2011) showed that broiler chicks fed on different levels of Bovine blood and rumen content mixture had no significant differences existed in the carcass characteristics of the birds.…”
Section: Carcass Traitsmentioning
confidence: 91%
“…Yitbarek et al (2016) showed that carcass characteristics of birds fed diets containing different levels of DBRCM were not statistically different in edible carcass yield comparing with the control group. Also, Esonu et al (2011) found that there were no significant differences in dressing percentage of birds fed diets containing mixture of fermented bovine blood and rumen digesta. Onu et al (2011) showed that broiler chicks fed on different levels of Bovine blood and rumen content mixture had no significant differences existed in the carcass characteristics of the birds.…”
Section: Carcass Traitsmentioning
confidence: 91%